Factors Affecting Users’ Acceptance on Enterprise Resource Planning Systems in Yemen Organizations - M. A. Al-Awlaqi; A. S. AlSanabani (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2019)
This study aims to unravel the factors that might have the potential to facilitate or hinder the Enterprise Resource Planning (ERP) system in the Yemen Organizations. Methods were done by interviewing 197 respondents from some Yemen organizations. The results of this study found significant positive correlationsbetween the intention to use and easiness of the ERP system. Several dependent variables were also obtained. Moreover, thecurrent study obtained the importance of human factors in thecontext of ERP.